Surveillance for COVID-19 in the English Football League 2019-2020. (16th November 2021) - Basu, Subhashis; Higgins, Richard; Malhotra, Aneil; Ahmad, Imtiaz
ABSTRACT: Medical surveillance and risk mitigation protocols to reduce viral transmission have underpinned the return of elite football during the COVID-19 pandemic. This article describes the evidence-informed approach and surveillance findings from the English Football League across a 9-week period at the end of the 2019–20 season. Protocols were devised by the lead EFL Medical Advisor with specialist occupational medicine input. Isolation requirements for cases and contacts were in-line with UK Government regulations, with external contact tracing conducted by local public health authorities. Quantitative PCR testing was conducted twice weekly and within 72 hours of fixtures. Forty-three individuals, including 18 players returned positive tests. No positive results were returned after week 5 (round 10). Our findings support those from other leagues that with appropriate compliance, elite football can continue safely during this pandemic. We recommend that protocols and compliance should be revised as necessary according to community prevalence and changes in viral transmission dynamics.